Mapping Research Orientations and Methodological Trends in Indonesian SINTA 1–Scopus-Indexed Translation Studies (2020–2025) - Pratiwi, Berlin Insan; Rakhmasari, Dwi Lia (Eralingua: Jurnal Pendidikan Bahasa Asing dan Sastra, 2026)
The growing recognition of translation as a multidimensional practice highlights the need for systematic mapping within translation studies. This study aims to map research orientations and methodological trends in SINTA 1–Scopus-indexed journals from 2020 to 2025, providing an empirical basis for situating Indonesia within the global development of translation studies. This study employed qualitative document analysis based on Holmes’s framework. It followed a PRISMA-guided scoping review process, identifying eight journals and screening 35 potentially relevant articles according to predefined criteria. After the eligibility assessment, 27 articles were retained for final analysis. A longitudinal analysis was conducted to reveal patterns and developments over time. The findings indicate a continued dominance of product-oriented research and qualitative approaches in Indonesian SINTA 1–Scopus-indexed translation studies articles, with limited use of quantitative and mixed methods. These results suggest that national research and publication trends remain largely concentrated on established textual analysis traditions and have not yet fully reflected the broader methodological and theoretical diversification observed at the global level. This study contributes both empirically and methodologically by mapping research orientations and methodological trends in Indonesian translation studies. It further highlights the gap between national practices and global developments, thereby contributing to a more nuanced understanding of uneven disciplinary development across contexts. These findings imply the need to expand methodological and analytical approaches, including corpus-based, process-oriented, and interdisciplinary research. They also underscore the importance of strengthening connections between research, academic publishing practices, and curriculum development, particularly through greater engagement with translation technology, professional practice, and competence-based education